Analysis of E-Commerce Adoption by SMEs Using the Technology - Organization - Environment (TOE) Model: A Case Study in Karawang, Indonesia - Setiyani, Lila; Yeny Rostiani (International Journal of Science, Technology & Management, 2021)
E-commerce as a medium for online transactions by business actors can increase the productivity of SMEs. This study aims to analyze the adoption of e-commerce in SMEs in Karawang Regency, Indonesia. The technology-organization-environment (TOE) framework was chosen as a variable for measuring e-commerce adoption. Data collection was carried out through a questionnaire survey which was distributed to SMEs in Karawang Regency, and obtained 301 respondents. The results of data collection by using Smart PLS with the results of the technological aspects have no significant effect on the intention to adopt e-commerce, while the organizational and environmental aspects have a significant effect on the intention to adopt e-commerce. All technology indicators, namely compatability, perceived usefulness, complexity, security concern and relative advantage, are proven to have a significant effect on technology in the intention to adopt e-commerce. Organizational indicators, namely cost, organization readiness, organization culture, organization size and top management support, are proven to have a significant effect on organizations in their intention to adopt e-commerce. Meanwhile, environmental indicators, namely government support, competitive pressure, environmental uncertainty and vendor quality, have a significant effect on the environment in the intention to adopt e-commerce. The data that has been generated can be used by the MSMEs management agency in Karawang Regency to formulate strategies for increasing the productivity of SMEs.